Trimethylolethane modified aqueous zinc ion battery electrolyte and aqueous zinc ion battery

By using trimethylolethane as an additive in aqueous zinc ion batteries, adsorbing on the surface of zinc negative electrode and controlling the double layer structure, the problems of zinc negative electrode dendrites and hydrogen evolution reaction are solved, and the cycle performance and life of the battery are significantly improved.

CN119601793APending Publication Date: 2025-03-11KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411734772.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Water-based zinc ion batteries face problems such as zinc negative electrode dendrite growth and hydrogen evolution reaction, which affect the cycling performance and life of the battery.

Method used

Trimethylolethane (TME) is used as an additive to regulate the electric double layer structure through its adsorption on the surface of the zinc negative electrode, and inhibit dendrites' growth and hydrogen evolution reaction.

Benefits of technology

It effectively inhibits the growth of zinc dendrites and hydrogen evolution reaction, extends the circulation time of zinc negative electrodes, and improves the device life of aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005161205500000011
    Figure HDA0005161205500000011
  • Figure HDA0005161205500000012
    Figure HDA0005161205500000012
  • Figure HDA0005161205500000021
    Figure HDA0005161205500000021
Patent Text Reader

Abstract

The invention discloses a trimethylolethane modified aqueous zinc ion battery electrolyte and an aqueous zinc ion battery. Wherein the aqueous zinc ion battery electrolyte comprises soluble zinc salt, trimethylolethane and water, after a trimethylolethane additive rich in polar groups (-OH) is introduced into the electrolyte, a zinc negative electrode can be covered by trimethylolethane molecules, and the adsorption of H2O is hindered, so that the side reaction is inhibited; and meanwhile, the adsorbed trimethylolethane adjusts the diffusion and nucleation behaviors of Zn < 2 + > on the surface of the negative electrode, and promotes the preferential deposition of a Zn (002) texture, so that dendrite-free Zn deposition is realized, and the problems of dendrite, hydrogen evolution, corrosion and the like of the current aqueous zinc ion battery negative electrode are solved. Besides, the trimethylolethane adsorbed on the surface of the electrode regulates the double electrode layer at the interface of the zinc negative electrode, so that the number of water molecules in the double electrode layer is reduced, the cycle time of the zinc negative electrode can be effectively prolonged, and the device life of the water-based zinc ion battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous zinc ion batteries, and in particular relates to an aqueous zinc ion battery electrolyte modified by a trimethylolethane additive. Background Art

[0002] Lithium-ion batteries have the advantages of high voltage and high energy density. However, they use a flammable organic electrolyte system inside, and lithium is very active, which poses a great safety hazard. In the case of overcharge, overdischarge, short circuit or external impact, the battery may experience thermal runaway, or even cause a fire or explosion. The safety issues of traditional lithium-ion batteries have forced people to consider developing other energy storage systems.

[0003] Aqueous zinc-ion batteries are considered to be one of the most promising alternatives to lithium-ion batteries due to their safety, environmental friendliness, low cost, and non-toxicity. In addition, zinc metal has an outstanding theoretical specific capacity (820 mAh g -1 ), impressive areal capacity (5855mAh cm -3 ), and can be directly used as the negative electrode due to its low redox potential (-0.76 V vs. standard hydrogen electrode). However, the practical application of metallic zinc as the negative electrode of aqueous zinc-ion batteries faces severe challenges related to zinc dendrite growth, hydrogen evolution reaction, surface passivation and electrode corrosion, which are closely related to the double-layer structure.

[0004] Electrochemical reactions occur in the double layer, which is crucial for evaluating the stability of the electrode. The double layer formed by the combination of water molecules and ions at the interface is the area where the electrochemical reaction occurs. The H2O molecules contained in the traditional double layer will participate in the hydrogen evolution reaction and lead to the formation of by-products. In order to alleviate these side effects, constructing a water-poor double layer is an idea to stabilize the zinc anode. It is reported that electrolyte additives can be selectively adsorbed on the anode to produce a water-poor double layer. In the electrochemical reaction process at the junction of the zinc anode and the electrolyte, desolvation and deposition phenomena always play a key role, and the occurrence of these phenomena depends on the chemical structure and characteristics of the double layer. In addition, under the repulsive effect generated by the double layer, the two-dimensional random diffusion of zinc ions promotes the extensive formation of zinc dendrites. Therefore, by reconstructing the double layer structure of the zinc anode and adjusting the interface environment between the electrode and the electrolyte, the battery life and its cycle performance can be significantly improved.

[0005] However, identifying suitable additives that can effectively regulate the double layer remains a daunting challenge. In previous studies, the potential impact of subtle changes in the adsorption morphology of additives on the double layer structure of the zinc negative electrode interface was often overlooked. In fact, the concentration fluctuations of adsorbed additives have a significant impact on the double layer, which is directly related to the performance of the entire battery. Therefore, in order to effectively solve the problems of hydrogen evolution side reactions and dendrite growth currently faced by aqueous zinc-ion batteries, the key lies in carefully selecting adsorbed additives and accurately controlling their concentrations to regulate the double layer interface of the zinc negative electrode to an ideal state. Summary of the invention

[0006] In view of the common problems of zinc negative electrode dendrite growth and hydrogen evolution reaction in aqueous zinc ion batteries, the first aspect of the present invention provides an aqueous zinc ion battery electrolyte modified with a trimethylolethane additive, which utilizes the adsorption of trimethylolethane on the surface of the zinc negative electrode to effectively inhibit zinc dendrite growth and interface side reactions, while regulating the zinc negative electrode interface double layer, extending the cycle time of the zinc negative electrode, and improving the device life of the aqueous zinc ion battery.

[0007] The aqueous zinc ion battery electrolyte provided in the first aspect of the present invention comprises a soluble zinc salt, trimethylolethane and water. The concentration of the soluble zinc salt may be 1 to 3 M, and the molar concentration ratio of the soluble zinc salt to the trimethylolethane may be 2:0.1 to 0.6, more specifically 2:0.2 to 0.6.

[0008] Preferably, the molar concentration ratio of the soluble zinc salt to the trimethylolethane is 2:0.3.

[0009] According to a specific embodiment of the present invention, the concentration of the soluble zinc salt is 2M; the concentration of the trimethylolethane is 0.1-0.6M, more specifically 0.2-0.6M.

[0010] Preferably, the concentration of trimethylolethane is 0.3M.

[0011] In the present invention, the soluble zinc salt can be one of zinc sulfate, zinc chloride, zinc bromide, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, zinc tetrafluoroborate, or a combination thereof.

[0012] According to a specific embodiment of the present invention, the aqueous zinc ion battery electrolyte consists of a soluble zinc salt, a trimethylolethane additive and water.

[0013] The second aspect of the present invention discloses an aqueous zinc ion battery using any one of the aforementioned aqueous zinc ion battery electrolytes.

[0014] Wherein, the positive electrode material of the aqueous zinc ion battery can be NH4V4O10 (ammonium vanadate), metallic zinc or copper, the negative electrode material is metallic zinc.

[0015] The beneficial effects of the present invention are:

[0016] (1) After adding trimethylolethane additives rich in polar groups (-OH) to the electrolyte of aqueous zinc-ion batteries, the zinc negative electrode can be covered by trimethylolethane molecules, which hinders the adsorption of H2O and thus inhibits side reactions; at the same time, the adsorbed trimethylolethane regulates the Zn 2+ The diffusion and nucleation behavior on the negative electrode surface promotes the preferential deposition of Zn(002) texture, thus achieving dendrite-free Zn deposition.

[0017] (2) Trimethylolethane adsorbed on the electrode surface can regulate the double layer at the zinc negative electrode interface, reduce the number of water molecules in the double layer, and thus improve the cycle stability of the aqueous zinc ion battery and the reversibility of the zinc negative electrode, effectively extend the cycle time of the zinc negative electrode, and improve the device life of the aqueous zinc ion battery.

[0018] (3) The present invention modifies the electrolyte by using trimethylolethane additive, has low preparation cost, simple and convenient preparation method, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The contact angles of 2M ZnSO4 and electrolytes with different concentrations of trimethylolethane additive on zinc foil are shown;

[0020] Figure 2 The current density is 1 mA cm -2 , with a capacity of 1 mAh cm -2 , the long-term galvanostatic cycling performance of Zn||Zn symmetric cells when the electrolyte is 2M ZnSO4 and different concentrations of trimethylolethane additive are added;

[0021] Figure 3 (a) Using 2M ZnSO4 + 0.3M trimethylolethane electrolyte, at a current density of 1mAcm -2 , capacity is 1 mAh cm -2 Digital photo of the Zn negative electrode surface in the Zn||Zn symmetric battery after 40 cycles. Figure 3 (b) and 3(c) are SEM images of the surface of the Zn negative electrode;

[0022] Figure 3 (d) Using 2M ZnSO4 electrolyte, at a current density of 1 mA cm -2 , capacity is 1 mAh cm -2 Digital photo of the Zn negative electrode surface in the Zn||Zn symmetric battery after 40 cycles. Figure 3 (e) and 3(f) are SEM images of the surface of the Zn negative electrode;

[0023] Figure 4 At a current density of 1 mA cm -2 , with a capacity of 1 mAh cm -2 , XRD patterns of Zn negative electrode of Zn||Zn symmetric battery after 5 cycles when the electrolytes are 2MZnSO4 and 2M ZnSO4+0.3M trimethylolethane respectively;

[0024] Figure 5 The chronoamperometric curves of the Zn||Zn symmetric cell at a constant overpotential of -150 mV using 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane electrolytes;

[0025] Figure 6 The electrochemical double layer capacitance of zinc negative electrode in 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane electrolyte;

[0026] Figure 7 (a) and (b) are the adsorption modes and corresponding adsorption energies of H2O and TME on the Zn(002) surface, respectively; (c) and (d) are the coordinated Zn in 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane electrolytes, respectively. 2+ The radial distribution function and coordination number of (e) are snapshot sections of the MD simulation of the TME dynamic formation simulation perpendicular to the Zn surface;

[0027] Figure 8 At a current density of 5 mA cm -2 , with a capacity of 1 mAh cm -2 , Coulombic efficiency of Zn||Cu asymmetric cells using 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane electrolytes;

[0028] Fig. 9 The Zn||NH4V4O electrolyte using 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane is shown. 10 Full battery at 0.5Ag -1 Cycle performance under

[0029] Fig.10 The Zn||NH4V4O electrolyte using 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane is shown. 10 The rate performance of the battery. DETAILED DESCRIPTION

[0030] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0031] The aqueous zinc ion battery electrolyte of the embodiment is composed of a soluble zinc salt such as zinc sulfate, a trimethylolethane (TME) additive, and water, wherein the concentration of the soluble zinc salt is 2M (mol L -1 ), the concentrations of trimethylolethane additive are 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M and 0.6 M. Ultrapure water or deionized water is preferably used.

[0032] The preparation process of aqueous zinc ion battery electrolyte in the embodiment is as follows:

[0033] Step 1: Dissolve 5.7512 g of zinc sulfate heptahydrate in 10 mL of deionized water at 25° C. to completely dissolve into a clear solution. The concentration of this solution is 2 M and is recorded as solution A (solution A is also used or described as a comparative example electrolyte).

[0034] Step 2: 0.1238 g, 0.2477 g, 0.3715 g, 0.4954 g, 0.6193 g and 0.7431 g of trimethylolethane additive were added to 6 portions of the same A solution, and ultrasonicated until completely dissolved to obtain the aqueous zinc ion battery electrolyte of the embodiment. Correspondingly, the concentrations of the trimethylolethane additive in the embodiment were 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M and 0.6 M, respectively.

[0035] Other components, such as sorbitol, xylitol, etc., can be further added to the aqueous zinc ion battery electrolyte of the embodiment. Sorbitol, which is rich in hydroxyl groups, is used as an electrolyte additive, which can strongly interact with water molecules and zinc electrodes, thereby customizing the hydrated Zn 2+ The solvation sheath of the ions adjusts the surface of the zinc electrode and improves the wettability with the Zn electrode. This can effectively inhibit the dendritic growth and harmful side reactions on the surface of the Zn electrode. The polyhydroxy xylitol molecules can be preferentially adsorbed on the surface of the zinc negative electrode, constructing a solid electrolyte interface layer that regulates the diffusion and deposition of zinc ions, uniformly distributing the interfacial electric field and ion flux, and effectively inhibiting dendrite growth and side reactions.

[0036] The aqueous zinc ion battery of the present invention can be: (1) an aqueous zinc ion Zn||Zn symmetric battery assembled with zinc foil as positive and negative electrodes and glass fiber as a separator; (2) an aqueous zinc ion Zn||Cu asymmetric battery assembled with zinc foil as negative electrode, copper foil as positive electrode and glass fiber as a separator; (3) an aqueous zinc ion Zn||Cu asymmetric battery assembled with zinc foil as negative electrode, glass fiber as separator and NH4V4O 10(Ammonium vanadate) was loaded on titanium foil as the positive electrode as the active material, and the assembled aqueous zinc ion Zn||NH4V4O 10 Full battery.

[0037] like Figure 1 As shown in (g), the 2M ZnSO4 electrolyte has a large contact angle of 57.8° on the zinc foil surface, which is mainly due to the hydrophobicity of the zinc foil, which can resist the wetting of the electrolyte. Figure 1 As shown in (a) to (f), after adding trimethylolethane additive to 2M ZnSO4, the wettability of the electrolyte is improved. Specifically, when the concentration of trimethylolethane additive in the electrolyte increases from 0.1M to 0.3M, the contact angle decreases with the increase of the concentration of the additive;. When the concentration of trimethylolethane additive increases from 0.4M to 0.6M, the contact angle increases with the increase of the concentration of the additive, and the wettability decreases. Among them, when the concentration of trimethylolethane additive is 0.3M, it has the smallest contact angle of 34.6°, that is, when the concentration of trimethylolethane additive is 0.3M, the electrolyte exhibits the highest wettability to zinc foil. It is worth noting that this improved wettability is conducive to promoting the reversible plating / stripping of zinc at the electrode / electrolyte interface.

[0038] like Figure 2 As shown, the 2M ZnSO4+trimethylolethane electrolyte exhibits significantly improved stability compared to the 2M ZnSO4 electrolyte. -2 and 1mAh cm -2 When using 2M ZnSO4 electrolyte, the life of the Zn||Zn symmetric battery is only 120 hours, while the life of the Zn||Zn symmetric battery is significantly extended when using the electrolyte with trimethylolethane additive, especially when using the electrolyte containing 0.3M trimethylolethane additive, it shows a high cycle stability of 1495 hours. This shows that the trimethylolethane additive can effectively inhibit the growth of zinc dendrites and interface side reactions, extend the cycle time of the zinc negative electrode, and improve the device life of the aqueous zinc ion battery.

[0039] pass Figure 1 and Figure 2 The results all indicate that the best effect is achieved when the concentration of trimethylolethane additive is 0.3M. The following only analyzes and compares 2M ZnSO4 electrolyte and 2M ZnSO4+0.3M trimethylolethane electrolyte in detail.

[0040] Figure 3 (a) and (d) are the results of the experiment at a current density of 1 mA cm -2 , with a capacity of 1 mAh cm -2Digital photograph of the Zn negative electrode surface of the Zn||Zn symmetric battery after 40 cycles in 2M ZnSO4+0.3M trimethylolethane and 2M ZnSO4 electrolyte. Figure 3 (a) The surface of the zinc foil is smooth, while Figure 3 In (d), the surface of the zinc foil is black, which is the result of the accumulation of the by-product Zn4SO4(OH)6·xH2O on the surface of the zinc foil.

[0041] In addition, the surface of the negative electrode zinc foil after 40 cycles was tested by scanning electron microscopy (SEM). Figure 3 (b) and 3(c), Figure 3 (b) clearly shows that the surface of the zinc foil presents a flat and dense appearance. Figure 3 (c) It can be seen that the surface has a flat hexagonal close-packed morphology, which is consistent with the characteristics of the Zn (002) crystal plane. This indicates the existence of the Zn (002) texture, which in turn indicates that the trimethylolethane additive effectively prevents the growth of Zn dendrites at the anode / electrolyte interface. However, after 40 cycles in 2M ZnSO4 electrolyte, as shown in Figure 3 As shown in (e) and (f), vertical, irregular byproducts and Zn dendrites appeared on the Zn anode interface.

[0042] Figure 4 At a current density of 1 mA cm -2 , with a capacity of 1 mAh cm -2 The XRD patterns of the Zn negative electrode of the Zn||Zn symmetric battery after 5 cycles when the electrolytes were 2M ZnSO4 and 2M ZnSO4+0.3M trimethylolethane. Figure 4 As shown in Figure 2, the diffraction peaks at ≈36.3, 39.0, and 43.2 degrees can be pointed to the (002), (100), and (101) planes of Zn (PDF#04-0831), respectively. It is worth noting that compared with the 2M ZnSO4 electrolyte, after adding 0.3M trimethylolethane, I (002) with I (101) The ratio of Zn to Mg increased from 0.52 to 0.91, indicating that Zn 2+ It prefers to deposit on the (002) plane and is not easy to form irregular dendrites. This confirms that Zn 2+ The homogenization of the flux and uniform nucleation / growth of Zn also indicate that the trimethylolethane additive helps to guide the growth of Zn (002) crystal plane.

[0043] like Figure 5As shown, chronoamperometric tests were performed at -150 mV to evaluate the effect of trimethylolethane additive on Zn nucleation and growth. The current density continued to increase in the 2M ZnSO4 electrolyte due to the well-known “tip effect”, which implies uncontrolled two-dimensional diffusion and inhomogeneous dendrite growth. In contrast, the presence of trimethylolethane led to a fast nucleation process and produced a more stable current, indicating that Zn 2+ The two-dimensional diffusion is restricted, resulting in uniform crystal growth.

[0044] like Figure 6 As shown in the figure, the double layer capacitance of the Zn electrode was calculated at different rates by cyclic voltammetry to analyze the effect of trimethylolethane additive on the interfacial behavior. The linear fitting results show that the double layer capacitance of the Zn negative electrode surface in 2M ZnSO4 electrolyte is 263.05 μF cm -2 In 2M ZnSO4+0.3M trimethylolethane electrolyte, the double layer capacitance of the Zn negative electrode surface dropped to 209.97 μF cm -2 The decrease in the value of the double-layer capacitance indicates that the adsorption of the trimethylolethane additive on the Zn negative electrode surface leads to the expansion of the double layer, which means that the double layer originally filled with H2O is now occupied by trimethylolethane molecules, and the H2O molecules are expelled from the inner Helmholtz plane, which is beneficial to improve the utilization of zinc and the stability of the battery cycle.

[0045] like Figure 7 As shown in (a) and 7(b), the adsorption energy of Zn(002)-TME is -0.77eV, which is significantly higher than the adsorption energy of Zn(002)-H2O -0.31eV, indicating that TME has a significant affinity for the Zn surface. Specifically, TME molecules are preferentially adsorbed on the surface of the zinc negative electrode, which is beneficial to reduce the number of H2O molecules in the inner double layer. Figure 7 As can be seen from (c) and 7(d), trimethylolethane did not change the Zn 2+ The solvation structure of Figure 7 As shown in (e), after the introduction of trimethylolethane into the electrolyte, the TME molecules gradually migrated to the surface of the Zn negative electrode during the relaxation process and occupied part of the H2O position in the double layer, further confirming that trimethylolethane tends to accumulate on the surface of the Zn negative electrode and leads to a decrease in the water content of the double layer. In summary, the trimethylolethane additive regulates the double layer structure by adsorbing on the surface of the Zn negative electrode, effectively inhibiting the growth of zinc dendrites and interfacial side reactions, extending the cycle time of the zinc negative electrode, and improving the cycle life of aqueous zinc ion batteries.

[0046] like Figure 8 As shown, the Zn||Cu asymmetric battery using 2M ZnSO4+0.3M trimethylolethane electrolyte exhibits a stable Zn2+ The stripping / plating process lasted for more than 600 cycles with an average CE of 99.79%. In contrast, the Zn||Cu asymmetric cell using 2MZnSO4 electrolyte exhibited poor cycling stability and reversibility, with significant coulombic efficiency fluctuations after 242 cycles, which may be due to uncontrollable dendrite growth and side reactions.

[0047] like Fig. 9 As shown, Zn||NH4V4O using 2M ZnSO4+0.3M trimethylolethane electrolyte 10 The specific capacity of the full battery after 600 cycles is 113.39 mAh g -1 , the capacity retention rate is 42.91%. In contrast, Zn||NH4V4O 10 The specific capacity of the full battery after 600 cycles is 73.16 mAh g -1 , the capacity retention rate is only 25.79%.

[0048] like Fig.10 As shown, Zn||NH4V4O using 2M ZnSO4+0.3M trimethylolethane electrolyte 10 The rate performance of the full cell is better than that of Zn||NH4V4O using 2M ZnSO4 electrolyte 10 Full battery.

[0049] In summary, the present invention adopts a safe and low-cost method to effectively solve the problems of dendrite growth, hydrogen evolution reaction and corrosion faced by the negative electrode of current aqueous zinc ion batteries, and thus develops a high-performance aqueous zinc battery. This innovation not only promotes the development of zinc batteries in the direction of low cost and high performance, but also greatly accelerates the pace of commercial application of aqueous zinc batteries.

[0050] This invention was supported by the National Natural Science Foundation of China (Project No. 52364041) and the Yunnan Outstanding Youth Fund (Project No. 202401AV070011).

[0051] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A trimethylolethane-modified aqueous zinc ion battery electrolyte, characterized in that: The aqueous zinc ion battery electrolyte comprises a soluble zinc salt, trimethylolethane and water.

2. The aqueous zinc ion battery electrolyte according to claim 1, wherein: The molar concentration ratio of the soluble zinc salt to the trimethylolethane is 2:0.1-0.

6.

3. The aqueous zinc ion battery electrolyte according to claim 2, characterized in that: The molar concentration ratio of the soluble zinc salt to the trimethylolethane is 2:0.

3.

4. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of the soluble zinc salt is 1-3M.

5. The aqueous zinc ion battery electrolyte according to claim 4, characterized in that: The concentration of the soluble zinc salt is 2M, and the concentration of the trimethylolethane is 0.1-0.6M.

6. The aqueous zinc ion battery electrolyte according to claim 5, characterized in that: The concentration of the trimethylolethane is 0.3M.

7. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The soluble zinc salt is one of zinc sulfate, zinc chloride, zinc bromide, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, and zinc tetrafluoroborate, or a combination thereof.

8. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The aqueous zinc ion battery electrolyte consists of soluble zinc salt, trimethylolethane and water.

9. An aqueous zinc ion battery, characterized in that: Use the aqueous zinc ion battery electrolyte described in any one of claims 1 to 8.

10. The aqueous zinc ion battery according to claim 9, characterized in that: The positive electrode material of the aqueous zinc ion battery is NH4V4O 10 , metallic zinc or copper, the negative electrode material is metallic zinc.

Citation Information

Cited By

  • Soluble chromium salt modified aqueous ion battery electrolyte

    CN121076273A